THE ROLE OF HARMONY BETWEEN HUMANS AND NATURE IN LANDSCAPES IN THE DEVELOPMENT OF ECOLOGICAL TOURISM (Scientific journal of the Fergana State University, 2026)
The article discusses the harmony of man and nature, the role of man in changing the appearance of landscapes, the ecotourism potential of natural and anthropogenic landscapes, and the concept of sustainable development.